Analysis of the Importance and Performance of Cost Information in Pricing Decisions in Ready-to-Eat Food Retail MSE in Vitória-ES - Dumer, Miguel Carlos Ramos; Souza, Beatriz Rebuli Serpa Peçanha; Lee, Viviane Nunes Tetzlaff; Guanandy, Francesca Nossa; da Silva, Vitor Correa; de Mendonça, Mark Miranda; de Souza Júnior, Roberto Rodrigues (Archives of Business Research, 2024)
Currently, decision-making is the major challenge for managers in the day-to-day operations of the company. It depends on various factors to be assertive and achieve positive results. We can say that pricing has become one of the fundamental decisions to be made. With that said, this work aimed to examine the relationship between the importance attributed and the effective knowledge of cost information for decision-making in setting prices in Micro and Small Enterprise (MSE) of ready-to-eat foods in Vitória-ES, from the perspective of managers. To do this, the methodology adopted was through quantitative methods and bibliographic research, based on the daily reality of small and medium-sized enterprises. We can analyze through raw data, collected with the help of standardized tools and a specific target audience. Firstly, the work presents a brief account of the importance of micro and small retail companies of ready-to-eat foods for the economy, the importance of cost accounting in pricing, and the conceptualization of the Slack Matrix used in the analysis of the raw results obtained, followed by the methodology and interpretation of the data collected from the managers.